EVALUASI IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM MENGATASI KEMISKINAN MASYARAKAT NELAYAN (STUDI KASUS NELAYAN TRADISIONAL DESA BENDAR, KECAMATAN JUWANA, KABUPATEN PATI) - Diah Meitasari; Budi Setiyono; Achmad Taufiq (Journal of Politic and Government Studies, 2015)
Poverty in Indonesia, one of them comes from fishery sector because the fishermen are minimal in the fulfillment of clothes, foods, shelters, health and education altough Indonesia has a total sea area of about 3.544 million km2 and has a huge potential for fisheries. The Ministry of Maritime Affairs may overcome the poverty in fishery sector through the developing of Program Usaha Mina Perdesaan (PUMP). Therefore, the formulation of the problem in this research is "How does the evaluation of PUMP Bendar Village, Juwana Sub- district, District of Pati, in alleviating the poverty of fishermen communitiy?".This study aimed to describe the evaluation of the program implementation of PUMP in Bendar Village, Juwana Sub- district, District of Pati and problems that occur in the field with its solutions, thus it can be known how far PUMP program can alleviate poverty of fishermen community in Bendar village. The method used is descriptive qualitative. The primary data source is obtained through interviews with a purposive sampling and secondary data from documents, archives, internet, and other sources associated with the research. Analysis techniques are qualitative data analysis with data reduction, data presentation and drawing conclusion or verification .Based on results of the research, it is known that PUMP program (Program Usaha Mina Perdesaan) is implemented in Bendar village in 2011. This PUMP program overcomes poverty in the form of cash money assistance amount to 100 million rupiahs that must be spent in the form of fishing gear, repair nets, purchasing of machinery or repair the engine, so this program is expected to create prosperity. PUMP program had been implemented in Bendar Village, but the level of prosperity of its citizen has not changed significantly since its members had lacking awareness to develop KUB.Advises that can be given are increased quality of human resources involved, socialization to Bendar Village communities about PUMP program that should be enhanced and maximized. The improving of cooperation in all elements both leader and member of fishermen groups in Bender Village is aimed to lessen negative perspective of bureaucracy in fishery bureau, so the citizen ready to develop KUB which may bring prosperity for them.Keywords: PUMP Program, Poverty, Bendar Village